Acceptability of Sodium-Reduced Research Diets, Including the Dietary Approaches to Stop Hypertension Diet, among Adults with Prehypertension and Stage 1 Hypertension - KARANJA, NJERI (2007)
OBJECTIVE: Examine the acceptability of sodium-reduced research diets. DESIGN: Randomized crossover trial of three sodium levels for 30 days each among participants randomly assigned to one of two dietary patterns. PARTICIPANTS/SETTING: Three hundred fifty-four adults with prehypertension or stage 1 hypertension who were participants in the Dietary Approaches to Stop Hypertension (DASH-Sodium) outpatient feeding trial. INTERVENTION: Participants received their assigned diet (control or DASH, rich in fruits, vegetables, and low-fat dairy products), each at three levels of sodium (higher, intermediate, and lower) corresponding to 3,500, 2,300, and 1,200 mg/day (150, 100, and 50 mmol/day) per 2,100 kcal. MAIN OUTCOME MEASURES: Nine-item questionnaire on liking and willingness to continue the assigned diet and its level of saltiness using a nine-point scale, ranging from one to nine. STATISTICAL ANALYSES PERFORMED: Generalized estimating equations to test participant ratings as a function of sodium level and diet while adjusting for site, feeding cohort, carryover effects, and ratings during run-in. RESULTS: Overall, participants rated the saltiness of the intermediate level sodium as most acceptable (DASH group: 5.5 for intermediate vs 4.5 and 4.4 for higher and lower sodium; control group: 5.7 for intermediate vs 4.9 and 4.7 for higher and lower sodium) and rated liking and willing to continue the DASH diet more than the control diet by about one point (ratings range from 5.6 to 6.6 for DASH diet and 5.2 to 6.1 for control diet). Small race differences were observed in sodium and diet acceptability. CONCLUSIONS: Both the intermediate and lower sodium levels of each diet are at least as acceptable as the higher sodium level in persons with or at risk for hypertension.